(untitled) (European Journal of Health Research, 2018)
The present study is a longitudinal study that tries to verify whether the perinatal risk levels of a group of preterm children can influence in their cognitive abilities in the school-age. Methods: The participants were divided in groups according to their level of perinatal risk which was obtained by means of PERI. The final sample was tested with the WISC-IV Scale. Results: The results show differences in the scores of low risk children, being higher in three subtests of the WISC-IV Scale. Notwithstanding, the scores are found to be lower in the group of high-risk children. Discussion: The results are discussed in the light of existing studies.